Odpowiedzi

2010-02-02T20:41:29+01:00
Uklad rownan:
36+1-12a-2b+c=0
4+25+4a-10b+c=0
36+1+12a+b+c=0

-12a -2b +c = -37
4a -10b =c = -29
12a +b + c = - 37

z ostatniego równania obliczam c
c= -37 -12a -b i podstawiam do pierwszego i drugiego równania

-12a -2b -37 -12a -b = -37
4a -10b -37 -12a -b = -29

12a -2b-12a -b = -37 +37
4a -10b -12a -b = -29 + 37

-24a -3b = 0 /:(-3)
-8a -11b = 8

b = -8a
-8a -11*(-8a) = 8

b = -8a
-8a + 88a = 8

b = -8a
80a = 8

b = -8a
a = 8 : 80

b = -8a
a = 0,1


b = -8*0,1 = -0,8
a = 0,1

a= 0,1
b = -0,8

c = -37 -12*0,1 + 0,8
c = -37 -1,2 + 0,8
c = -37 - 0,4
c = -37,4

a = 0,1
b = - 0,8
c = -37,4